The comparison of TiNiNbTa and TiNiNbV SMAs in terms of corrosion behavior, microhardness, thermal and structural properties - Balci, Esra; Dagdelen, Fethi (Springer, 2022)
In this study, Ti-27Ni-19Nb-4Ta and Ti-27Ni-19Nb-4 V (at./%) alloys were produced by arc-melting alloyed. The thermal properties of alloys were investigated by differential scanning calorimeter (DSC). The DSC results showed that the phase transformation temperatures of the Ta-added alloy were significantly higher than the V-added sample. Also, the Ta-added sample showed B19(/) -> R -> B2 phase transformation, while the V-added sample exhibited B19(/) -> B2 phase transformation in two steps. When TiNiNbTa and TiNiNbV SMAs are compared, it is seen that the Ta-added sample exhibits a better corrosion resistance. In addition, beta-Nb phase was found in the dendritic structures of the alloys in scanning electron microscopy-energy-dispersive X-ray spectroscopy(SEM-EDX) analysis. Using the X-ray diffraction(XRD) results, the crystallite size for TiNiNbTa and TiNiNbV samples was found as 33.76 and 46.86 nm, respectively. It was determined that the microhardness of the V-added alloy was much higher than the Ta-added alloy.
Keywords: Shape memory alloy; Corrosion resistance; NiTi alloy; Crystallite size